Suggestions for the management of general surgery patients during the Covid-19 health emergency - Trujillo-Loli, Yeray (2020)
The objective of this paper is to present suggestions for the preoperative, intraoperative, and postoperative management of general surgery patients during the COVID-19 health emergency, aiming to minimize risks for surgeons and to reduce in-hospital transmission of SARS-CoV-2. We reviewed the literature using the PubMed database and we also reviewed websites from international scientific societies and the Peruvian Ministry of Health website. Suggestions for the management of surgical patients are proposed, based on the experience of countries with larger numbers of COVID-19 cases. We emphasize the importance of the adequate use of personal protective equipment (PPE), and the feasibility of using an open or laparoscopy approach in emergency surgical procedures, taking adequate care in order to avoid viral transmission for both the patient and healthcare personnel. Nonetheless, we must consider that recommendations may vary with time as new knowledge is acquired.